2018
DOI: 10.1111/jcpt.12729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of lanthanum carbonate hydrate on the pharmacokinetics of roxadustat in non‐elderly healthy adult male subjects

Abstract: SummaryWhat is known and objective: Roxadustat is a hypoxia-inducible factor prolyl hydroxylase inhibitor currently being investigated for the treatment of anemia in chronic kidney disease. Lanthanum carbonate is a phosphate binder that is commonly used to treat hyperphosphatemia in patients with chronic kidney disease. This study investigated the effect of lanthanum carbonate on the pharmacokinetics, safety and tolerability of a single oral dose of roxadustat in healthy non-elderly adult male subjects. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The AUC 0-∞ of roxadustat was 12% lower when roxadustat was administered concomitantly with lanthanum carbonate compared with roxadustat administered alone, whereas the mean C max , median t max , and mean t ½ were comparable when roxadustat was administered alone or concomitantly with lanthanum carbonate. 14 The current study indicated that calcium acetate significantly reduces roxadustat's exposure when coadministered with roxadustat, likely because of chelation with calcium ions. However, a study evaluating the effect of food on the pharmacokinetic properties of roxadustat found that administration of a single dose of 100 mg roxadustat given concomitantly with a meal that contained 184 mg of calcium did not result in a significant change in the AUC of roxadustat compared with its administration under fasted conditions.…”
Section: Discussionmentioning
confidence: 60%
“…The AUC 0-∞ of roxadustat was 12% lower when roxadustat was administered concomitantly with lanthanum carbonate compared with roxadustat administered alone, whereas the mean C max , median t max , and mean t ½ were comparable when roxadustat was administered alone or concomitantly with lanthanum carbonate. 14 The current study indicated that calcium acetate significantly reduces roxadustat's exposure when coadministered with roxadustat, likely because of chelation with calcium ions. However, a study evaluating the effect of food on the pharmacokinetic properties of roxadustat found that administration of a single dose of 100 mg roxadustat given concomitantly with a meal that contained 184 mg of calcium did not result in a significant change in the AUC of roxadustat compared with its administration under fasted conditions.…”
Section: Discussionmentioning
confidence: 60%
“…[69][70][71][72][73]75,76 Roxadustat and daprodustat are primarily oxidized by cytochrome P450 (CYP) 2C8, with a c l i n i c a l i n v e s t i g a t i o n VH Haase: HIF-PH inhibitors for anemia of CKD minor contribution of CYP3A4 to daprodustat metabolism. 81,82 In addition to CYP2C8-mediated oxidation, roxadustat undergoes phase 2 hydrophilic modification by glucuronidation and glucosidation. 75,83 Enarodustat is also metabolized by CYP enzymes, 72 whereas molidustat and vadadustat are primarily metabolized by uridine 5 0 -diphospho-glucuronosyltransferases.…”
Section: Pharmacokinetic Profilesmentioning
confidence: 99%
“…The pharmacokinetics of roxadustat after oral administration are well characterized (Table 1 ) and appear to be linear (Yu [ 71 ], Groenendaal [ 26 , 27 ], Groenendaal [ 28 ], Shibata [ 62 ], Shibata [ 63 ], Provenzano [ 55 ], Rekic [ 59 ], Groenendaal [ 29 , 30 ], Takada [ 67 ]). Roxadustat is readily absorbed after oral administration, has a moderate apparent volume of distribution, and is eliminated largely by metabolism (cytochrome P450 (CYP) 2C8, UDP-glucuronosyltransferase (UGT) 1A9).…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%
“…Omeprazole had no clinically relevant effect on roxadustat pharmacokinetics [ 28 ]. Furthermore, lanthan and spherical carbon adsorbent had no clinically relevant effect on roxadustat pharmacokinetics [ 62 , 63 ]. Roxadustat did not influence warfarin [ 27 ].…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%